The comparison of antifungal susceptibility of C. glabrata, C. tropicalis, C. parapsilosis, C. krusei and C. kefyr isolated from different sources - Grabiec, Alicja; Krzemińska-Jaśkowiak, Elżbieta; Cybulski, Zefiryn; Talaga, Zofia (Contemporary Oncology/Współczesna Onkologia, 2003)
Yeast-like fungi have become more important as an infection factor especially in immunocompromised patients, including those afflicted with malignant neoplasms. Materials and methods. The antifungal susceptibility to 5-fluorocytosine, amphotericin B, nystatin, miconazole, econazole and ketoconazole of C. glabrata, C. tropicalis, C. parapsilosis, C. krusei and C. kefyr isolated both from hospitalised patients and out- -patients was compared. The yeasts were cultured on Albicans ID2 agar and Sabouraud medium and were identified with the use of ID32C biochemical test kit. ATB FUNGUS tests were used for the examination of sensitivity to antifungal drugs. Results. The strains most commonly found among non-albicans yeasts (NAC) isolated from cancer patients were 36 C. glabrata and 14 C. tropicalis – 57% and 22%, respectively. C. parapsilosis and C. glabrata were most often isolated strains from out-patients – 37% and 33%, respectively. Forty nine (77.8%) strains isolated from in-patients showed 222222 sensitivity pattern (sensitivity to all the antifungal drugs tested) and seven (26%) out-patients strains showed the same sensitivity pattern. Two strains of C. glabrata isolated from hospitalised patients were resistant to 5-fluorocytosine, nystatin, econazole and ketoconazole. One strain of C. krusei isolated from an out-patient was resistant to amphotericin B. Conclusions 1. The examination of species and sensitivity patterns of NAC isolates is useful for finding identical strains. 2. Some strains were found to be resistant to amphotericin B, a drug often used in hospital environment. 3. The results of antimycograms may be used both for choosing antifungal drugs and for the epidemiological investigation.